2013
DOI: 10.5507/bp.2012.101
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NT-proBNP levels in hemodialysis versus peritoneal dialysis patients

Abstract: Background. Plasma N-terminal fragment of pro brain natriuretic peptide (NT-proBNP) concentration is elevated in cardiovascular diseases such as congestive heart failure, where increased levels of NT-proBNP indicate cardiac dysfunction, hypervolemia, and higher risk of hospitalization and death. These associations apply also to patients with severe impairment of kidney function. Little is known about diferences in plasma level of NT-proBNP in patients receiving hemodialysis (HD) versus those receiving continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“… 29 A study performed by Ludka et al. 30 showed that the mean absolute level of NT-proBNP in patients on HD was 2281 ± 1710 pmol/L, which was significantly higher than the normal level. In the present study, we established ROC curves to explore the optimal NT-proBNP cutoff value in patients on maintained HD, according to the recommended BP, ultrafiltration/dry weight ratio, and hemoglobin values from the KDIGO and KDOQI guidelines.…”
Section: Discussionmentioning
confidence: 94%
“… 29 A study performed by Ludka et al. 30 showed that the mean absolute level of NT-proBNP in patients on HD was 2281 ± 1710 pmol/L, which was significantly higher than the normal level. In the present study, we established ROC curves to explore the optimal NT-proBNP cutoff value in patients on maintained HD, according to the recommended BP, ultrafiltration/dry weight ratio, and hemoglobin values from the KDIGO and KDOQI guidelines.…”
Section: Discussionmentioning
confidence: 94%
“…Except for the primary cardiovascular diseases, the increase of volume load in the PD group should be fully considered, which was consistent with the findings of previous reports. [11][12][13][14] Consequently, patients should be advised to control the amount of water intake. Diuretics should be appropriately administered to reduce the capacity load, improve the heart function, and reduce the hospitalization rate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observed correlation with eGFR was more marked for NT-proBNP than for BNP, and the ratio of NT-proBNP/BNP increased with advancing CKD stage [11]. A high NT-proBNP concentration has been shown to predict morbidity and mortality, and its concentration in patients undergoing CAPD is lower than those undergoing HD [12]. Additionally, NT-proBNP is a significant predictor of cardiovascular congestion, mortality, and adverse cardiovascular outcomes in PD patients [13].…”
Section: Correlation Between Bnp and Nt-probnp And Other Parametersmentioning
confidence: 98%
“…Cardiac biomarkers, such as BNP and NT-proBNP, are commonly used to diagnose CHF [11]. Pre-proBNP is synthesized in cardiac myocytes in response to ventricular wall stress and stretch, associated with greater cardiac filling pressure [12]. After the removal of a signal peptide in the cytosol, proBNP is released as either NT-proBNP or BNP from myocytes into the circulation [11,13].…”
Section: Correlation Between Bnp and Nt-probnp And Other Parametersmentioning
confidence: 99%